Determinants Of Height Coverage Of Children Just Entering Elementary School (Sd) In Puskesmas Wolojita And Puskesmas Onekore Ende District - Anggra Widianti; Lewi Jutomo; Intje Picauly; Yendris K Syamruth; Christina Olly Lada (Green Publisher Indonesia, 2024)
Stunting is a condition of failure to grow in children due to chronic malnutrition in the first 1000 days of life (HPK). The incidence of stunting in children can be caused by several factors, namely family income, history of infectious diseases, history of nutritional status, mother's education, parenting patterns, mother's knowledge, and food consumption patterns. The aim of this research is to determine the factors that determine the height coverage of children entering elementary school in Ende Regency. This type of research is quantitative with cross sectional research. A sample of 61 first grade elementary school students was selected using probability sampling. The research was conducted in August 2023-April 2024. Univariate and bivariate data analysis using the chi-square test. The test results showed the disease history factor (p-value : 0.027; ρ maternal knowledge about nutrition (p-value : 0.009; ρ x,y: 0.212; OR : 1.128; 95%CI : 0.003-3.131); consumption patterns (p-value : 0.002; ρ and nutritional status (p-value : 1 ; ρ of elementary school children in Ende Regency.